Sympathy and the Concept of Face in Frances Browne’s My Share of the World - Nagado, Madoka (Australasian Journal of Victorian Studies, 2021)
This article explores the concept of ‘face’ in an Irish blind poet Frances Browne’s fictional autobiography of a sighted person to examine how sympathy in the nineteenth-century sense of the word conditions disability narratives, and also how Otherness is constituted within them. If the act of imagining the lives of Others, in this case of blind persons, is a sympathetic act, how do we engage with their imaginings of the lives of the sighted? By taking the voice of a sighted person, Browne as a blind author questions abled people’s unconscious confidence that because they see more, they will necessarily be more perceptive than those who cannot see. Explicating the literary tropes in the novel, this article suggests how disability life writing can offer valuable ethical insights into how nineteenth-century British writers viewed themselves in relation to unrelated Others, and by extension, can illuminate how their readers could consider those not themselves.